Novel Imaging and Genetic Risk Markers in Takotsubo Syndrome - Arcari, Luca; Limite, Luca Rosario; Adduci, Carmen; Sclafani, Matteo; Tini, Giacomo; Palano, Francesca; Cosentino, Pietro; Cristiano, Ernesto; Cacciotti, Luca; Russo, Domitilla; Rubattu, Speranza; Volpe, Massimo; et al. (Frontiers in Cardiovascular Medicine, 2021)
Takotsubo syndrome (TTS) is an increasingly recognized condition burdened by significant acute and long-term adverse events. The availability of novel techniques expanded the knowledge on TTS and allowed a more accurate risk-stratification, potentially guiding clinical management. The present review aims to summarize the recent advances in TTS prognostic evaluation with a specific focus on novel imaging and genetic markers. Parametric deformation analysis by speckle-tracking echocardiography, as well as tissue characterization by cardiac magnetic resonance imaging T1 and T2 mapping techniques, currently appear the most clinically valuable applications. Notwithstanding, computed tomography and nuclear imaging studies provided limited but promising data. A genetic predisposition to TTS has been hypothesized, though available evidence is still not sufficient. Although a genetic predisposition appears likely, further studies are needed to fully characterize the genetic background of TTS, in order to identify genetic markers that could assist in predicting disease recurrences and help in familial screening.